Myocardial inflammation is associated with impaired mitochondrial oxidative capacity in ischaemic cardiomyopathy - Julius Borger; Elric Zweck; Constanze Moos; Patrick Horn; Fabian Voß; Heinz‐Peter Schultheiss; Jacob Eifer Møller; Udo Boeken; Hug Aubin; Artur Lichtenberg; Malte Kelm; Michael Roden; et al. (ESC Heart Failure)
Abstract Aims Myocardial inflammation and impaired mitochondrial oxidative capacity are hallmarks of heart failure (HF) pathophysiology. The extent of myocardial inflammation in patients suffering from ischaemic cardiomyopathy (ICM) or dilated cardiomyopathy (DCM) and its association with mitochondrial energy metabolism are unknown. We aimed at establishing a relevant role of cardiac inflammation in the impairment of mitochondrial energy production in advanced ischaemic and non‐ischaemic HF. Methods We included 81 patients with stage D HF (ICM, n = 44; DCM, n = 37) undergoing left ventricular assist device implantation (n = 59) or heart transplantation (n = 22) and obtained left ventricular tissue samples during open heart surgery. We quantified mitochondrial oxidative capacity, citrate synthase activity (CSA) and fibrosis and lymphocytic infiltration. We considered infiltration of >14 CD3+ cells/mm2 relevant inflammation. Results Patients with ICM or DCM did not differ regarding age (61.5 ± 5.7 vs. 56.5 ± 12.7 years, P = 0.164), sex (86% vs. 84% male, P = 0.725), type 2 diabetes mellitus (34% vs. 18%, P = 0.126) or chronic kidney disease (8% vs. 11%, P = 0.994). ICM exhibited oxidative capacity reduced by 23% compared to DCM (108.6 ± 41.4 vs. 141.9 ± 59.9 pmol/(s*mg), P = 0.006). Maximum production of reactive oxygen species was not significantly different between ICM and DCM (0.59 ± 0.28 vs. 0.69 ± 0.36 pmol/(s*ml), P = 0.196). Mitochondrial content, detected by CSA, was lower in ICM (359.6 ± 164.1 vs. 503.0 ± 198.5 nmol/min/mg protein, P = 0.002). Notably, relevant inflammation was more common in ICM (27% vs. 6%, P = 0.024), and the absolute number of infiltrating leucocytes correlated with lower oxidative capacity (r = −0.296, P = 0.019). Fibrosis was more prevalent in ICM (20.9 ± 21.2 vs. 7.2 ± 5.6% of area, P = 0.002), but not associated with oxidative capacity (r = −0.13, P = 0.327). Conclusions More than every fourth ICM patient with advanced HF displays myocardial inflammation in the range of inflammatory cardiomyopathy associated with reduced mitochondrial oxidative capacity. Future studies may evaluate inflammation in ICM at earlier stages in standardised fashion to explore the therapeutic potential of immunosuppression to influence trajectories of HF in ICM.